Representations of the modern girl in Japanese interwar literature - Kaynar, Aslı İdil. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study explores the Japanese modern girl’s (moga) representations in Taishō and early Shōwa texts, and the role these representations played in women finding their voice in literature. The project acknowledges the modern girl figure as a character of fiction and a real-life figure. Examining the modern girl’s position within the Japanese feminist writing, the study supports the idea that whereas the media wanted to turn her into a passive figure or a stereotype by objectifying her, literary texts’ portrayals of this figure are of great variety. The modern girl differs from her contemporary, the New Woman in that, The New Woman appeared before moga in 1910s as a politically active feminist figure, whereas moga was defined as passive. Moga drew attention due to her Westernized looks and the way she took an active part in the public space. For these reasons, she became an inspiration for many authors. Through context based analysis of Tanizaki Jun’ichirō’s and Uno Chiyo’s selected literary works, and Kawabata Yasunari’s The Scarlet Gang of Asakusa (Asakusa kurenaidan) this study reveals the common patterns in the protagonists’ relationships with the modern girl analyzed within the theoretical framework of objectification. This thesis argues that moga in real life was a complex figure that cannot be simply categorized as a product of mass culture. The study ends with the suggestion that there is still much to explore about the modern girl, especially through examining her representations in literary texts.
Keywords: Japanese literature.